Taking Sides: Urban Wandering as Decolonial Translation and Critique of Settler Colonialism - Price, Joshua Martin (Tusaaji: A Translation Review, 2020)
Abstract: Colonialism fragments meaning. This essay takes up colonial fragmentation of meaning as a question of translation. It offers a decolonial methodology to unpack the political stakes as one moves back and forth across the colonial line. The methodology is based on a conscious process of urban wandering or drifting, what the Situationists called the “dérive.” Two case studies of itinerant decolonial theorizing follow. The first is a sketch of the militarized border between the US and Mexico, and the second example has to do with Columbus Day/Indigenous Peoples’ Day. In the case studies, translating is treated as a question of “tuning in” as one tunes into a conversation, or, alternatively, as if into a radio frequency. The metaphor of translation-as-tuning-in allows us to address practical and concrete questions of translation in everyday settings, as well as contemporary theoretical debates in translation studies. Keywords: translation; colonialism; decolonial methodology; border; dérive